Nicotine concentration in the hair of nonsmoking mothers and size of offspring. - Nafstad, P (1998)
OBJECTIVES: The purpose of this study was to estimate the risk of small-for-gestational-age birth by levels of nicotine in the hair of mothers and offspring. METHODS: In a sample of 58 case subjects and 105 control subjects, hair nicotine concentrations were measured by gas chromatography and mass spectrometry. RESULTS: With women whose hair nicotine concentrations were in the lowest quartile as the reference group, the odds ratio (OR) for small-for-gestational-age birth was increased among women with concentrations in the upper and two middle quartiles (OR=4.2, 95% confidence interval [CI]=1.5, 11.5, and OR = 3.2, 95% CI=1.3, 8.0). When smoking mothers were excluded from the analysis, the corresponding odds ratios were 2.1 (95% CI=0.4, 10.1) and 3.4 (95 % CI= 1.3, 8.6). CONCLUSIONS: The results suggest that passive maternal smoking increases the risk of small-for-gestational-age births.